Model of Forming Purchase Intention For Skincare Products Through Tiktok Social Media With Theory of Planned Behavior Analysis - Nurul Fathin Siregar; Hartoyo; Mochammad Mukti Ali (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: Currently TikTok has become the most widely used social media application for online shopping, with beauty products securing the second position as the most frequently purchased category by consumers through social media platforms.Purpose: The aim of this research are to analyze the influence of content marketing, perceived value, and perceived risk on the Theory of Planned Behavior, and the model for forming the intention to purchase skincare products through the TikTok social media platform using the Theory of Planned Behavior.Design/methodology/approach: The data processing techniques used in this research are descriptive analysis and Structural Equation Model(SEM) analysis.Findings/Result: The research results indicate that the highest percentage in the content marketing variable is found in on brand, perceived value in hedonic value, perceived risk in product risk, attitude in safety, subjective norms in content creator/affiliator, and perceived behavioral control in convenience.Conclusion: Attitudes, subjective norms, and perceived behavioral control have a significant effect on the intention to purchase skincare products throughTikTok. Content marketing, perceived value, and perceived risk significantly affect attitudes. Content marketing significantly influences subjective norms, and perceived behavioral control is only influenced by perceived value.Originality/value (State of the art): In this study, purchase intention is viewed through content marketing (credible, shareable, useful or fun, interesting, relevant, different, and on-brand), perceived value (utilitarian value, hedonic value, and social value), perceived risk (transaction risk, delivery risk, and product risk), and based on the theory of planned behavior (attitude, subjective norms, and perceived behavioral control). This combination of theories is tested using SEM PLS to understand how consumers develop the intention to buy skincare products through TikTok Shop. Keywords: content marketing, perceived risk, perceived value, purchase intention, theory of planned behavior